Optimization of Gains and Variability during Selection of Candidate Plus Trees in Eucalyptus tereticornis Smith - Sircar, Sumita; Sindhu Veerendra, H. C. (Indian Forester, 2011)
A computerized index scheme was developed for selection of candidate plus trees in Eucalyptus tereticornis provenances and an overall increase in the yield in the volumetric traits was achieved in the selected population. To quantify the realized gains and thereby to test association of variability within each of selected population, several runs were conducted with different number of trees. Realized gains and level of variation exhibited strong associate ships. Selection of large number of trees decreases the gains but overall population variability was increased. As gains increased, level of variation was decreased. However, a trade-off existed between the two. Hence, the genotypes retain tbeir superiority. As an ideal strategy, a run with 66 candidate plus trees were selected which gives sufficient selection pressure allowing sufficient variation to float within the selected population. Total be ight exhibited a selection differential of 6.8 m with a se.lection pressure of 36.82%. Clear bole beight has a selection differential of 3.23 m and selection pressure of22.12%. Similarly, GBH bas selection differential of 27.73 cm and 68.17% selection pressure was exerted foUowed by number of branches with 4.94 and 65.6% selection differential and selection pressure respectively. The yield improvement is associated with lower co-efficient of variation indicating lower amount of population variability which facilitates formation of uniform plantations.